Performance of the manual and Sofia rapid antigen test in medical staff exposed to Omicron variants - Guanche Garcell, Humberto; Vargas Girón, Eduardo; Gonzalez Perez, Sandra Ibis; Felipe Garmendia, Angel M; Gutierrez Garcia, Francisco (International Journal of Infection Control, 2024)
Background: Variable COVID-19 rapid antigen test sensitivity had been reported and the effect of viral variants drew attention to the impact in the early detection of cases. Objective: The study aims to compare the performance of antigen tests (manual rapid antigen tests [RAT], and Sofia test) in medical staff exposed during the circulation periods of different Omicron variants. Methods: The descriptive study of samples collected for the diagnosis of SARS-CoV-2 infection included medical staff at The Cuban Hospital (TCH) Hospital repeated from December 2021 to December 2022, including cases confirmed by SARS CoV-2 polymerase chain reaction (PCR), and a RAT. December 2021–March 2022 and June-December 2022 were considered the periods of Omicron BA.1.1. variants and Omicron BA.4/5 respectively. Comparison of Ct figures between categories was carried out using the Wilcoxon–Mann–Whitney test, and sensitivity (95% confidence intervals [CI]) values were calculated. Results: 287 healthcare workers were diagnosed with COVID-19 during the study period, 56.1% during the B.1.1. variant period, and 43.9% when B.4/5 variants were predominantly in circulation. Sensitivity of the manual RAT test (82.5%; 95% CI 73.4–89.4) was higher during the B.1.1. variant circulation in comparison with the B.4/5 period (68.9%;53.4–81.8). These two methods during this B.4/5 period had quite similar sensitivity figures when compared to each other; manual 68.9% (95% CI 53.4–81.8) and Sofia 72.7% (95% CI 60.4–83.0). Conclusion: The variation in sensitivity of the RAT for SARS CoV-2 variants and the similar performance of manual and SOFIA methods of RAT could be considered in the diagnostic approach of COVID-19 and the appropriate isolation of potentially infectious cases.